2008
DOI: 10.1016/j.pain.2007.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Pain associated with multiple sclerosis: Systematic review and proposed classification

Abstract: Pain is common in patients with multiple sclerosis (MS), but estimates of its prevalence have varied widely. The literature describing pain in MS patients spans four decades and has employed a range of different methodologies. We undertook a systematic review in order to summarize current understanding of the association between MS and pain and provide a basis for the design and interpretation of future studies. The point prevalence of pain in patients with MS is nearly 50%, and approximately 75% of patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
368
1
30

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(443 citation statements)
references
References 93 publications
21
368
1
30
Order By: Relevance
“…This is consistent with published data reporting the prevalence range TN in multiple sclerosis from 1.6% to 18% [3,8,19,11,24]. The age of onset of multiple sclerosis-associated TN in patients has been noted to be about 10 years younger than in patients without multiple sclerosis [25][26][27].…”
Section: Characteristics Of Types Of Central Painsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with published data reporting the prevalence range TN in multiple sclerosis from 1.6% to 18% [3,8,19,11,24]. The age of onset of multiple sclerosis-associated TN in patients has been noted to be about 10 years younger than in patients without multiple sclerosis [25][26][27].…”
Section: Characteristics Of Types Of Central Painsupporting
confidence: 91%
“…Trigeminal neuralgia: After revision all our patients with TN confirmed criteria according Cruccu et al Our results showed TN to be present in 5.91% of multiple sclerosis patients, which is much higher than in general population (from 0.1% to 0.7%) [24]. This is consistent with published data reporting the prevalence range TN in multiple sclerosis from 1.6% to 18% [3,8,19,11,24].…”
Section: Characteristics Of Types Of Central Painsupporting
confidence: 91%
“…Pain is an important component of MS, which, despite its significant impact on patients' QoL, is often neglected or undertreated. Patients with MS present not only spontaneous pain, but also several forms of evoked pain such as cutaneous mechanical pain and cold hypersensitivity at the distal extremities [41,42]. Promising results in the treatment of pain have been reported for PEA in various clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2004 study by Solaro et al, 1 studies usually classify pain symptoms according to temporal criteria rather than the World Health Organization pain treatment guidelines. 2 The physical pain described by people with MS is often widespread, chronic, and debilitating. The types of physical pain associated with MS can vary depending on the area of the brain affected.…”
mentioning
confidence: 99%
“…The types of physical pain associated with MS can vary depending on the area of the brain affected. In 2008, O'Connor et al 2 proposed four classifications of MS-related pain: 1) continuous central neuropathic pain, 2) intermittent central neuropathic pain, 3) musculoskeletal pain, and 4) mixed neuropathic and non-neuropathic pain. Central neuropathic pain, which is pain experienced in the absence of any psychiatric disorder or peripheral neuropathic pain, is consistent with a CNS lesion and may affect between 27.5% and 58% of MS patients.…”
mentioning
confidence: 99%